Analysis of the Impacts of Socioeconomic Conditions on the Dropout Statuses of High School-Level Students in Malang City - Sari, Mulia; Fadjar, Nurman Setiawan (Journal of Development Economic and Social Studies, 2025)
This research examines the impact of socioeconomic conditions on dropout statuses at the high school level in Malang City. The study aims to fill the gap in understanding the factors influencing high school dropout rates by analyzing the relationship between various socioeconomic variables and the likelihood of students dropping out. Using logistic regression and firthlogit models, data from several districts in Malang City were analyzed to identify significant predictors such as parental education level, parental completeness, parental income, child employment status, and recipient status of the Indonesia Smart Program (PIP). The results show that low parental income and child employment status significantly increase the likelihood of students dropping out. In contrast, higher parental education levels, parental completeness, and PIP recipient status tend to lower the dropout risk. This research concludes that targeted policy interventions are needed to mitigate these risks. The implications contribute to educational policy, highlighting the importance of sustained financial and social support for students from low-income families.   Abstrak Penelitian ini mengkaji dampak kondisi sosial ekonomi terhadap status putus sekolah pada tingkat SMA di Kota Malang. Penelitian ini bertujuan untuk mengisi kesenjangan dalam memahami faktor-faktor yang mempengaruhi angka putus sekolah dengan menganalisis hubungan antara berbagai variabel sosial ekonomi dan kemungkinan siswa putus sekolah. Dengan menggunakan regresi logistik dan model firthlogit, data dari beberapa kabupaten di Kota Malang dianalisis untuk mengidentifikasi prediktor yang signifikan seperti tingkat pendidikan orang tua, kelengkapan orang tua, pendapatan orang tua, status pekerjaan anak, dan status penerima Program Indonesia Pintar (PIP). Hasilnya menunjukkan bahwa rendahnya pendapatan orang tua dan status pekerjaan anak secara signifikan meningkatkan kemungkinan siswa putus sekolah. Sebaliknya, tingkat pendidikan orang tua yang lebih tinggi, kelengkapan orang tua, dan status penerima PIP cenderung menurunkan risiko putus sekolah. Penelitian ini menyimpulkan bahwa diperlukan intervensi kebijakan yang tepat sasaran untuk memitigasi risiko-risiko tersebut. Implikasinya berkontribusi pada kebijakan pendidikan, menyoroti pentingnya dukungan finansial dan sosial yang berkelanjutan bagi siswa dari keluarga berpenghasilan rendah.